2008
DOI: 10.1159/000118738
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic screening of livestock populations in Europe: an overview

Abstract: Clinical animal cytogenetics development began in the 1960’s, almost at the same time as human cytogenetics. However, the development of the two disciplines has been very different during the last four decades. Clinical animal cytogenetics reached its ‘Golden Age’ at the end of the 1980’s. The majority of the laboratories, as well as the main screening programs in farm animal species, presented in this review, were implemented during that period, under the guidance of some historical leaders, the first of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
160
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(171 citation statements)
references
References 181 publications
3
160
0
8
Order By: Relevance
“…Unfortunately, knowledge on DSDs other than freemartinism in cattle is rather limited. Sex chromosome abnormalities responsible for DSD are not common in this species and X monosomy is almost absent, while cases of XXY, XYY, and XXX trisomies were reported rather rarely (Ducos et al 2008). There are very few reports on DSD females with a male karyotype (60,XY) and a lack of the SRY gene (Kawakura et al 1996;Payan-Carreira et al 2008).…”
Section: Resultsmentioning
confidence: 71%
“…Unfortunately, knowledge on DSDs other than freemartinism in cattle is rather limited. Sex chromosome abnormalities responsible for DSD are not common in this species and X monosomy is almost absent, while cases of XXY, XYY, and XXX trisomies were reported rather rarely (Ducos et al 2008). There are very few reports on DSD females with a male karyotype (60,XY) and a lack of the SRY gene (Kawakura et al 1996;Payan-Carreira et al 2008).…”
Section: Resultsmentioning
confidence: 71%
“…Ducos et al (2008) published a survey of the cytogenetic screening of livestock populations in Europe. Developments in omics technologies may help overcome some limitations of traditional breeding programmes (Berry et al, 2011), but databases of phenotypes will be still necessary.The paper sums up the studies done in the Czech cattle population, and focuses on the various aspects of the genetic health.…”
Section: Introductionmentioning
confidence: 99%
“…The observed problems in parentage of this sire with DNA from blood could be clarified with DNA from semen. The most reported cytogenetic phenomena in cattle are XX/XY chimerism (Ducos et al, 2008;Peretti et al, 2008) and the Robertsonian translocation (Ducos et al, 2008;Iannuzzi et al, 2008;Vozdova et al, 2008). Therefore, blood chimersim can lead to mapping problems, especially in small populations, and therefore, exclusion and detection of chimera, at least in the sires of any research project, should be done, as it was already suggested for embryo transfer calves (Morris et al, 2009).…”
Section: Introductionmentioning
confidence: 99%